A novel multiple membrane blood‐feeding system for investigating and maintaining Aedes aegypti and Aedes albopictus mosquitoes. Issue 2 (December 2014) - Luo, Yi‐Pey
ABSTRACT A novel multiple membrane blood‐feeding system for mosquitoes has been developed for the study and routine maintenance of Aedes aegypti L. and Aedes albopictus Skuse that require a meal of vertebrate blood to produce eggs. This blood‐feeding system uses cattle collagen sausage‐casing membrane to facilitate feeding. The efficiency of this blood‐feeding system was compared to a live mice blood source. We observed that Ae. aegypti that fed on pig whole blood had 89.7% (w/o ATP) and 90.7% (w/ ATP) blood‐feeding rates, which were not significantly different from the mice‐fed ones (98.0%). Ae. albopictus fed on pig whole blood (w/ ATP) had a success rate of 84.4%, which was significantly different from the mice‐fed mosquitoes (51.1%). The feeding rates did not differ between sausage‐casing membrane and Parafilm‐M®. The survival rate, fecundity, pupation, and pupal emergence rates of Aedes females fed on pig whole blood were not significantly different from the mice‐fed ones. The artificial blood feeder can be applied to replace live animals as blood sources. Considering that this simple, inexpensive, convenient, and efficient feeding device can be built with common laboratory materials for research on Aedes mosquitoes.